A micropower low-distortion digital pulsewidth modulator for a digital class D amplifier - Bah, Hwee Gwee (2009)
We describe the design of a micropower digital pulsewidth modulator (PWM) for a hearing instrument Class D amplifier. The PWM embodies a novel delta-compensation (έC) sampling process and a novel pulse generator. The C process is sampled at the same low rate as reported algorithmic sampling processes and it features a similar low total harmonic distortion(THD). Its arithmetic computation is however, substantially simplified. We analytically derive the double Fourier series expression for the C process and show that the THD is low. The pulse generator is based on a hybrid 9-b counter 3-b tapped-delay-line. We investigate the compromise between the different design parameters that affect its power dissipation and THD. The complete proposed PWM features a simple circuit implementation (small IC area), micropower low voltage operation ( 22.1 µW@ 1.1 V), low sampling rate (48 kHz) and low harmonic distortion ( 0.2%), thereby rendering it suitable for a practical digital hearing instrument. We verify our design by means of computer simulations and on the basis of experimental measurements.